Clinical Preventability of 30‐Day Readmission After Percutaneous Coronary Intervention. Issue 5 (26th September 2014) - Wasfy, Jason H.; Strom, Jordan B.; Waldo, Stephen W.; O'Brien, Cashel; Wimmer, Neil J.; Zai, Adrian H.; Luttrell, Jennifer; Spertus, John A.; Kennedy, Kevin F.; Normand, Sharon‐Lise T.; Mauri, Laura; Yeh, Robert W.
Abstract : Background: Early readmission after PCI is an important contributor to healthcare expenditures and a target for performance measurement. The extent to which 30‐day readmissions after PCI are preventable is unknown yet essential to minimizing their occurrence. Methods and Results: PCI patients readmitted to hospital at which PCI was performed within 30 days of discharge at the Massachusetts General Hospital and Brigham and Women's Hospital were identified, and their medical records were independently reviewed by 2 physicians. Each reviewer used an ordinal scale (0, not; 1, possibly; 2, probably; and 3, definitely preventable) to rate clinical preventability, and a total sum score ≥2 was considered preventable. Characteristics of preventable and unpreventable readmissions were compared, and predictors of clinical preventability were assessed by using multivariate logistic regression. Of 9288 PCIs performed, 9081 (97.8%) patients survived to initial hospital discharge and 1007 (11.1%) were readmitted to the index hospital within 30 days. After excluding repeat readmissions, 893 readmissions were reviewed. Fair agreement between physician reviewers was observed (weighted κ statistic 0.44 [95% CI 0.39 to 0.49]). After aggregation of scores, 380 (42.6%) readmissions were deemed preventable and 513 (57.4%) were deemed not preventable. Common causes of preventable readmissions included staged PCI without new symptoms (14.7%), vascular/bleeding complications of PCI (10.0%), and congestive heart failure (9.7%). Conclusions: Nearly half of 30‐day readmissions after PCI may have been prevented by changes in clinical decision‐making. Focusing on these readmissions may reduce readmission rates.